Factors Influencing the Effectiveness of Information System Implementation Among Small and Medium Manufacturing Enterprises in Malaysia (Malaysian Management Journal, 2009)
This study examined information system (IS) effectiveness and its influence factors in the specific context of small and medium manufacturing enterprise (SME). The model evaluated the importance of manager participation in IS implementation, manager IS knowledge and accounting knowledge, and external experts (vendors, consultants, government agencies, and accounting firms) for IS effectiveness. The sample included 232 SMEs registered with the Federation of Malaysian Manufacturers. The results showed that manager accounting knowledge, and the effectiveness of vendors and accounting firms, are essential for IS effectiveness. Overall, the results suggested that managers of SMEs need to acquire sufficient accounting knowledge to help them better understand business information requirements. Secondly, SMEs should engage qualified vendors who have experience and understand unique characteristics of SMEs to overcome their lack of IS knowledge. SMEs should also exploit their good relationship with accounting firms to help them implement effective IS. Finally, it is important for SMEs to learn from their IS implementation so that opportunities can be recognised and priority given to initiatives that help IS support their information needs.